Influencia de la violencia familiar en el abandono de las y los residentes en el albergue infantil "Hogar de Esperanza" - distrito Salaverry:2016. - Reyes de la Cruz, Mirian Rita (2016)
This thesis was performed with the purpose to analyze the influence of family violence in the abandonment of the and residents in the Hostel Children "Home of Hope" - District Salaverry: 2016. It has been considered the type of descriptive research, and the sample consisted of 65 children and adolescents of both sexes, with whom we worked by applying the methods and techniques of quantitative and qualitative investigation. The results obtained can be deduced that family violence has generated psychological abuse, sexual and physical, generating serious moral hazard in the and residents in the Hostel children considered as the unit of analysis. The conditions of the family violence that generate child abandonment include a history of abuse in the home of origin, feelings of inferiority, low self-esteem and need for control over the environment, etc. Finally we believe that you have to perform and interdisciplinary and intersectoral intervention to resolve the problem of family violence and child abuse.